HISTOPATOLOGYCAL BRONKIOLUS AND BLOOD VESSEL OF MICE LUNG POST EXPOSURE OF ELECTRIC CIGARETTE SMOKE - Monica, Mia; Adi, Anak Agung Ayu Mirah; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana, 2019)
This study aims to determine the histopathological changes of bronchioles and blood vessel of mice (Mus musculus) lung post exposed of electric cigarette smoke (vaping) . This study was used 24 mice that were divided into two treatment groups. Group I (P0) as a control without electronic cigarette smoke exposured and group II (P1) consistied of 12 mice as a treatment group, were exprosure with electric cigarette smoke. This study used a complete randomized design (RAL) split in time pattern with three 1st, 2nd and 3rd post-treatment sampling times. Four mice of each group were taken at each observation time. Lung tissue was taken to make preparations and stained with Hematoxylin-eosin (HE) staining. The results showed that there were significant differences (P <0.05) between the treatment group and the control group, but the duration of exposure did not have an effect. Mucosal thickness in the treatment group was higher than in the control group (P <0.05). Vessel lung endothelins and thrombosis. It can be concluded, exposure to electric cigarette smoke can cause degeneration, cell necrosis and increase the mucosal thickness of the bronchioles. The vascular system experiences endotheliosis, endothelial cell necrosis and thrombosis